Exotic origins: the emblematic biogeographies of early modern scaly mammals. Issue 1 (13th July 2015) - Lawrence, Natalie
Abstract : Exotic natural objects brought to Europe in the sixteenth and seventeenth centuries were mutable and malleable things. They were constructed and assimilated into European world-views in a reciprocal process of change as they moved around early modern Europe. In particular, the provenance of natural objects and the associated rich symbolic resonances were central to their natural histories. The distinctions between Orient and Occident had divided the world since antiquity and were given a range of new senses in this period. The location of these two 'Indies', and their relationship to one another, were neither static nor always geographically defined. This article focuses on two rich examples of this natural historical construction in relation to images of the Indies: the Old World pangolin, or scaly anteater, and its New World counterpart, the armadillo. Initially, pangolins were understood as East Indian 'scaly lizards', armadillos as West Indian. But from the late seventeenth and early eighteenth centuries, their geographical identities and symbolic associations were entangled as these creatures came to embody colonial anxieties and resonances. The 'India' of the scaly lizard became the 'Indies' of the scaled mammals, both East and West. Examining the reception and treatment of examples such as these in European cabinets and natural histories, offers new insights into European relationships with regions of the world seen as distant and wonderfully bountiful.